HLA-DR1, Circulating Th1/Th2 Cytokines and Immunological Homunculus in Coronary Atherosclerosis - Amrollah Mostafazadeh; Mehrdad Saravi; Haleh Akhavan Niaki; Jos Drabbels; Haji Mohammad Gholipour; Milad Minagar; Ezatola Mosavi; Farzad Jalali; Ali Bijani (Iranian Journal of Allergy, Asthma and Immunology, 2011)
Coronary  atherosclerotic  disease  is  one  of  the  most  endangering  health  disorder worldwide. This study was designed to investigate the correlation between HLA-DRβ1 alleles and circulating Th1/Th2 type cytokines in coronary atherosclerosis. By Elisa, Th1/Th2 type cytokines were determined in serum samples of 31 subjects with unstable angina, 27 subjects with chronic stable angina and 24 individuals as normal control. By SSP-PCR, more than 100 alleles of HLA-DRB1 were typed in 24 subjects who had skewed serum levels of Th1/Th2 type cytokines. Lipid profiles were determined by the routine methods of clinical laboratory in all subjects. The  mean  serum  concentration  of  IL-10  in  normal  control  subjects  was  higher  in comparison to the patient groups.0.33±0.59 pg/ml versus 0.064±0.3 pg/ml in unstable angina pectoris group (p<0.028) and 0.22±0.6 pg/ml in chronic stable subjects. There was no statistically significant difference among the groups in serum levels of other desired cytokines  (IFN-γ,  IL-4).  33.33%  of  normal  control  subjects  were  HLA-DR16  positive whereas none of the subjects with chronic stable angina or individuals with unstable angina pectoris was positive for this antigen. The mean concentration of serum LDL-cholesterol in normal control group was high 142.046±35.40 (pg/ml). This preliminary study shows that the atherogenic effect of the LDL- cholesterol may be dampened by HDL-cholesterol through anti inflammatory cytokine IL-10 and HLA-DR16, a phenomenon interpretable via immunological homunculus theory.